The Humanitarian Action Qualifications Framework: a quality assurance tool for the Humanitarian Sector - Bastiaan L. Aardema; Cristina Churruca Muguruza (Tuning Journal for Higher Education, 2014)
The article presents the European Universities on Professionalisation on Humanitarian Action (EUPRHA) Project as an initiative that seeks to contribute to the professionalisation and quality assurance of the humanitarian sector. Its purpose is to explain the approach and the process leading to the development of the Humanitarian Action Qualifications Framework as an example of good practice for other sectors aiming at improving the recognition of qualifications as a precondition of academic and professional mobility. With this aim, it introduces the educational and humanitarian trends that led to this project: the move from transnational qualifications frameworks of which the European Qualifications Framework for Lifelong Learning (EQF) is the best example to sectoral qualifications frameworks and the increasing demand from the sector seeking to determine the competencies and required skills of a professional humanitarian aid worker. Based on the EQF and the Tuning methodology the framework will act as a translating device to make national and sectoral qualifications more readable and promote humanitarian workers’ and learners’ mobility between countries and organisations. It will facilitate inter-system transparency and recognition of (non-)formal and informal learning by linking occupations, skills, competences, and qualifications, thus benefiting the Humanitarian Sector as a whole.